Pengaruh Augmented Reality sebagai Media Pembelajaran terhadap Minat Belajar Siswa Mata Pelajaran IPA SD Kota Bengkulu - Yessi Oktaviani; Herman Lusa; Feri Noperman (Universitas Bengkulu, 2019)
This study aims to determine the effect of the utilization of Augmented Reality as a medium of learning on student interest in science subjects of Class IV SD in Bengkulu City. This research uses quantitative approach with experimental research type. The research method used is quasi experimental method with research design of maching only pretest-posttest control group design. The population in this study is all students of grade IV of SD Kota Bengkulu using KTSP curriculum. The sample in this research is the students of grade IVB SDN 82 amounting to 23 students is the experimental class and the IVA class of 24 students is the control class. The instrument used in this research is a questionnaire that uses Likert scale given through pretest that is before the learning takes place and posttest after the learning takes place. Data from this study were analyzed using descriptive analysis, and prerequisite test with normality test, homogeneity test, and inferential analysis. From result of research known result of t-test with tcount value of 10,52 and ttable value equal to 1,673. So with tcount (10,52)> ttable (1,673) at 5% significant level, it can be concluded that there is influence of utilization of Augmented Reality as a learning media to student's interest in science class IV SD Bengkulu City.